(untitled) (Świat Idei i Polityki, 2006)
The paper shows the current debates about globalization with special emphasis on the most controversial issues such as the impact of that process on the global welfare and economic development of the individual countries and the rise of transnational corporations which have become in some spheres more influencial than nation states. It focuses on not only one, positive aspect of globalization while entirely neglecting the negative one. This article examines various approaches to globalization and various definitions of that concept. The enormous number of such definitions and the mounting volume of literature on globalization has brought about such a paradoxical situation in which the more we read about globalization, the less clear we seem to be about what is means and what it implies. There are various types of globalization which are discussed in this paper including economic globalization, cultural and political one. While economic globalization refers mostly to changes in capital and labour flows, production systems and trade in goods and services, so political globalization refers to the changing global context of political awareness, processes and activity. It also can be perceived as a growing tendency for managing globalization and finding global solutions for the global problems which creates globalization. The open question is to what extent globalization can be considered as a process which has weakened nation states due to the growth of economic power of transnational corporations and other alternative international organizations and movements. The effects of globalization are the most visible in trade and capital flows, but they go beyond. Unfortunately they are evaluated not only on the basis of available historical experiences, facts and statistical data but also depend on the ideological background of a given author. There is no doubt that globalization has removed many barriers hindering the economic development in the global scale and has a huge potential to expand freedom, democracy, innovation and social and cultural exchanges. However, globalization has reinforced mostly the strong countries and societies and further weakened the weak ones. Therefore it should be reformed or humanized in order to secure sustainable economic and social development if not for all people in the world so for the majority of people.